Luxury and pleasure in eighteenth-century Britain - Berg, Maxine, 1950- (OUP E-Books., 2005)
The fine mahogany secretaire with its secret drawers, the lacquered tea table, Chinese and Japanese porcelain tea ware. These fine luxury goods now seem to belong to the English country house or the exclusive antique shop. But what do they tell us about their eighteenth-century consumers? Who owned these goods, what made them desirable, where did they come from, and how were they made? And how many people actually enjoyed their novelty and fashion? In Luxury and Pleasure in. Eighteenth-Century Britain Maxine Berg explores not only how luxury consumer goods transformed the homes of Britain's ur.